Urban health and health equity in Latin American cities: what COVID-19 is teaching us. (21st July 2021) - Diez Roux, Ana V.; Barrientos-Gutierrez, Tonatiuh; Caiaffa, Waleska Teixeira; Miranda, J. Jaime; Rodriguez, Daniel; Sarmiento, Olga Lucía; Slesinski, S. Claire; Vergara, Alejandra Vives
ABSTRACT: Latin America is the most unequal and urbanized region of the world. The physical and social environments of Latin American cities, the lack of public health and health-care infrastructure, and pronounced social and health inequities make these cities especially vulnerable to COVID-19. It is too soon to know the true impact of the pandemic and how it will compare to the many ongoing health and environmental challenges facing Latin American cities. In this commentary, we highlight a few key lessons with major implications not only for COVID-19 but for urban health and health inequities, that are beginning to emerge.